The author(s) declare that this Analisis Perspektif Hukum Persaingan Usaha Indonesia dalam Kasus Penyalahgunaan Posisi Dominan oleh Platform Digital TikTok Shop vs Shopee - Rahman, Novia Salsabila Ayuni; Abdul Basit; Ezza Padmaratri; Firza Agung Prakoso (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study evaluates the legal perspective concerning business competition in Indonesia regarding alleged abuse of dominant power in the competition between digital platforms TikTok Shop (including the acquisition of Tokopedia) and Shopee. The method applied is normative juridical with a case study approach, referring to Law Number 5 of 1999, particularly Articles 19–21 related to market control and Article 20 concerning below-cost selling practices. The analysis focuses on inter-platform integration, aggressive discount strategies, use of cross-platform data, as well as post-acquisition behavior that may hinder healthy competition. The assessment is conducted by considering market structure, business actors' behavior, and law enforcement efforts by the Business Competition Supervisory Commission (KPPU). Research findings indicate that although TikTok Shop has strong competitiveness following the acquisition, proving the existence of abuse of a dominant position requires meeting legal and economic provisions rigorously. Therefore, the implementation of conditional approval and remedial measures by the KPPU is considered a reasonable step to maintain a healthy business competition environment in the digital era.